2019
DOI: 10.2169/internalmedicine.1516-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Anti-MDA5 Antibody-positive Rapidly Progressive Interstitial Lung Disease without Signs of Dermatomyositis

Abstract: Anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody is associated with rapidly progressive interstitial lung disease (RP-ILD) in patients with clinically amyopathic dermatomyositis (CADM) or dermatomyositis (DM). We herein report three Japanese cases of anti-MDA5 antibody-positive RP-ILD without signs of CADM or DM. High-resolution computed tomography revealed patchy or subpleural distribution of consolidations and/or ground-glass opacities accompanied by traction bronchiectasis. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
(25 reference statements)
4
23
0
Order By: Relevance
“…The clinical features of our patients mostly presented with respiratory symptoms such as dyspnoea or cough at initial presentation, These findings were similar to other case reports [3,4,6,7]. However, some patients also had the cutaneous manifestations of CADM which were detected by physicians at first visit.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The clinical features of our patients mostly presented with respiratory symptoms such as dyspnoea or cough at initial presentation, These findings were similar to other case reports [3,4,6,7]. However, some patients also had the cutaneous manifestations of CADM which were detected by physicians at first visit.…”
Section: Discussionsupporting
confidence: 89%
“…Anti-MDA5 antibody is a type of myositis-specific autoantibody and reported to be a prognostic marker of RP-ILD in patients with CADM [4,5]. RP-ILD is associated with high mortality rates of up to 50%, especially within six months of diagnosis [2,3]. To our knowledge, limited data are available from case reports of patients with CADM-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Like our two patients, at least one of them had anti-SSA 52 antibodies (18), which are frequently associated with anti-MDA5 antibodies (10) and seem to be correlated with severe forms of ILD (2,20). As illustrated by our patient #2, some cases may present with RP-ILD and poor or no cutaneous, articular or muscle involvement (2,21), making diagnosis even more tricky and may delay proper support.…”
Section: Discussionsupporting
confidence: 51%
“…5,6 Interstitial lung disease (ILD) is a severe complication, with a reported prevalence of 5% to 65%. 7,8 Our previous retrospective cohort study showed that ILD occurred in 57% of patients with ADM. 9 The disease course and severity of ILD is highly heterogeneous, 10 and some patients with mild ILD remain stable and responsive to treatment, while other patients undergo rapidly progressive ILD (RPILD), which is usually refractory to treatment and leads to poor outcomes. 11,12 Despite aggressive conventional treatments, >50% of patients with ADM with RPILD die of respiratory failure within 1 year, especially in East Asia.…”
mentioning
confidence: 99%